Mexico : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that economic activity in Mexico accelerated to 3.8 percent in the first half of 2004 over the previous year. This recovery is partly attributable to strengthening U.S. industrial production, as reflected in growth in Mexican manufactured exports of 10 1\2 percent (seasonally adjusted) in the first seven months of 2004 over the same period in 2003. The government has made significant progress in strengthening the structure of public debt. Several liability management operations have helped to improve the efficiency of the yield curve.